Pertanggungjawaban Hukum bagi Pelaku Tindak Pidana Kekerasan Seksual terhadap Anak - Mulyadi, Mulyadi; Sujono, Sujono; Sudarto, Sudarto (LITERATUS, 2025)
The imposition of criminal penalties for the crime of child molestation should require the judge to consider the consequences arising from the act, both the psychological and psychological aspects of the victim, so that in his decision he can satisfy the sense of justice for the victim and the community. Seeing this reality, criminal law should provide appropriate sanctions for the perpetrators of the crime so that the supremacy of law is truly upheld and order is created in society. The research method used is normative juridical law. The results of the study are Legal responsibility for perpetrators of sexual violence against children that the first form of responsibility is of course, criminal responsibility carried out by adult perpetrators which can be seen in the provisions of Article 82 Paragraph (1) must be viewed as inseparable from Article 76E of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The form of legal protection against objects faced by objects and the implementation of Restitution from the perpetrator, that restitution is a form of material legal protection. The perpetrator of the crime or third party is responsible for replacing the loss by providing fair restitution to the victim of the crime, his family or dependents. Restitution includes the return of property or payment for damage or loss suffered and the restoration of rights